IDENTIFYING GRADE X STUDENTS’ PROBLEMS IN LEARNING ENGLISH VOCABULARY AT SMAN 1 PALASA PARIGI MOUTONG - Safira, Safira (Datokarama English Education Journal, 2025)
This research aimed to identify the problems faced by Grade X students in learning English vocabulary at SMAN 1 Palasa Parigi Moutong, with a focus on Grade X C students as the research subjects. The study employed a qualitative descriptive method, involving 29 students selected from a total population of 153. The instruments used to collect data were a questionnaire consisting of 13 questions and interviews with 8 questions. The findings revealed five main categories of difficulties experienced by the students: (1) challenges in memorizing long and complex vocabulary, indicating limited memory capacity and the absence of effective learning strategies; (2) difficulties in translating English texts, which stemmed from limited vocabulary mastery, insufficient grammatical understanding, and an inability to comprehend sentence context; (3) problems in spelling, caused by discrepancies between English pronunciation and spelling; (4) pronunciation difficulties, particularly due to the presence of silent letters and inconsistencies between spelling and pronunciation; and (5) obstacles in accurately using vocabulary in sentences, especially in selecting the correct verb tense and appropriate prepositions. These results indicated that students’ vocabulary mastery required significant improvement across various aspects, including memory retention, spelling, pronunciation, comprehension, and contextual usage. Therefore, a more contextualized, integrative, and sustainable approach to teaching English vocabulary was needed at the secondary school level.